SEKULERISASI POLITIK DAN ULAMA DI INDONESIA DALAM PRESFEKTIF AHMAD SYAFII MAARIF - Putri Wulansari (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2018)
Maaruf Amin As we know, it is the Chairman of the MUI (Indonesian Ulema Council) as well as the political elite among the Nadhiyin community. Surely he has an appeal in targeting Muslim voters. Moreover, NU, which is the largest Islamic mass organization in Indonesia, opened a wide road to the Jokowi-Maaruf Amin pair, strolling towards the Palace. Choosing and choosing or declaring their ideological or political choices is a part of human rights that cannot be contested, so that the involvement of ulamas in politics both as council and regional and central leaders is legitimate. However, when this involvement is placed in the context of practical politics or identity politics that can threaten the harmony of the life of the nation in the framework of diversity and unity. So the terminology of ulama and political secularization will be the right to realize the humanized and civilized Indonesia. Considering that ulama (Islam), pastors and other religious leaders have a role as spiritual teachers, they should focus on educating the nation not to be easily dragged into the heat of politics or identity politics, instead of competing to declare their support to make it a political fatwa. instead it fools and injures democracy and political rights of others. Keywords: Politics, Secularization, Ulama